Dr. J. Simon Ivey — Deep Plane Facelift — Maui - Ivey, J. Simon (DEEPPLANE™, 2026)
Surgeon profile record for Dr. J. Simon Ivey, practicing in Maui, USA. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003234; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; usa; maui